SOME KINDS OF COASTAL AND SEA SPACE RESOURCES IN VIETNAM - Thanh, Tran Duc (Vietnam Journal of Marine Science and Technology, 2007)
Recently, the space resources have been reported in the management documents; however, there have been not researches on the scientific basis for definition of these resources, yet. For the first time, this paper mentioned the sea space resources in Vietnam, and could be regarded as a first step for the further discussions. Referencing international literatures and starting from realistic awareness, it is realizes that the marine resources in Vietnam composes of living, non – living and sea space. The sea space resources could be defined as the benefits from an area or a site on sea, or in coastal zone, and situated in the spatial relations of this area or site. The sea space resources includes living and non living components, however, their key benefits must be get from values of sea/land forms and their spatial situations. The principal space resources in Vietnam Sea can be determined such as systems of water bodies or geosystems under the state sovereignty. They are included the coastal areas, islands, coastal bodies of water, offshore waters with the components of land (or bottom), water and air. This paper presented some concrete kinds of sea space resources included estuary, lagoon, coastal bay and island with the general estimation on developmental potentials.